The Potential Of Promise Waterfall as A Tourist Attraction in The Context of Tourism Development In Baktiraja, Humbang Hasundutan Regency - Triwanci Sinaga; Mian Siahaan; Dearlina Sinaga (International Journal of Management and Business Economics, 2026)
This study aims to analyze the potential of Janji Waterfall as a tourist attraction to boost tourism in Baktiraja Subdistrict, Humbang Hasundutan Regency. The research method employed was descriptive qualitative, using observation, interviews, and documentation. The results of the study indicate that Janji Waterfall possesses significant potential in terms of natural beauty (attractions) and adequate accessibility; however, amenities, management, and promotion remain suboptimal. These conditions have resulted in the number of tourist visits not yet increasing significantly. Supporting factors include natural potential and community involvement, while inhibiting factors consist of limited facilities and promotion. Therefore, development is needed through improved facilities, sustainable promotion, and cooperation between the government and the community so that tourism can develop optimally